Learning to serve: social learning and organizational customer orientation–employee job performance link in Nigerian service firms - Teng, Da; Song, Wei; Wang, Weiyue (Frontiers in Psychology, 2025)
Organizational Customer Orientation (OCO) refers to an organization’s continuous and proactive disposition that puts the interests of customers first. Extant studies have explored the relationship between OCO and employee job performance. However, the results are mixed and inconsistent. Collecting a set of multisource data at different points of times in Nigeria, this research advances the literature by arguing that Employee Customer Orientation (ECO) acts as a mechanism between OCO and employee job performance. Moreover, we argue that this mediation effect is moderated by the employee’s personality trait of openness to experience. The results support the view that, as expected, ECO mediates the effect of OCO on employee job performance. And, this mediating effect is moderated by the employee’s openness to experience. From a managerial perspective, our findings highlight the importance of an organizational climate for customer orientation and the management of employee – working environment interactions.